Posthuman and Personhood: Legal Ambiguity of Robo Spiens, Corporate and Nature in Jeanette Winterson’s The Stone Gods - Tan, Qi; Huang, Yuwei; Wu, Yun (Journal of Theory and Practice of Social Science, 2023)
Posthumanism is frequently associated with the concept that humans are no longer mere biological entities, but rather intricate and multifaceted beings endowed with distinctive characteristics and abilities. Conversely, legal personhood pertains to the status of individuals or organizations as legal entities possessing rights and responsibilities under the law. This encompasses their capacity to engage in contractual agreements, own property, initiate or be subject to lawsuits, and receive specific protections under legal frameworks. Both ideologies emphasize the significance of individual autonomy and agency while simultaneously challenging conventional notions of humanity. What’s more, the Stone Gods portrays nature, corporations, and robo sapiens as entities endowed with a certain "legal personhood" during the posthuman era, igniting fervent debates on whether we should bestow such status upon these non-human beings. This article delves into the legal ambiguity surrounding personhood for non-humans in this futuristic era, aiming to further explore the rational potential of dynamic legal personhood for the future.